Heat Transfer Enhancement in a Receiver Tube of Solar Collector Using Various Materials and Nanofluids - Guerraiche, D.; Guerraiche, K.; Driss, Z.; Chibani, A.; Merouani, S.; Bougriou, C. (Engineering, Technology & Applied Science Research, 2022)
The solar flux distribution on the Parabolic Trough Collector (PTC) absorber tube is extremely non-uniform, which causes non-uniform temperature distribution outside the absorber tube. Therefore, it generates high thermal stress which causes creep and fatigue damage. This presents a challenge to the efficiency and reliability of parabolic trough receivers. To override this problem, we have to homogenize the heat flux distribution and enhance the heat transfer in the receiver’s absorber tube to improve the performance of the PTC. In this work, 3D thermal and thermal stress analyses of PTC receiver performance were investigated with a combination of Monte Carlo Ray-Trace (MCRT), Computational Fluid Dynamics (CFD) analysis, and thermal stress analysis using the static structural module of ANSYS. At first, we studied the effect of the receiver tube material (aluminium, copper, and stainless steel) on heat transfer. The temperature gradients and the thermal stresses were compared. Second, we studied the effect of the addition of nanoparticles on the working Heat Transfer Fluid (HTF), employing an Al2O3-H2O based nanofluid at various volume concentrations. To improve the thermal performance of the PTC, a nanoparticle volume concentration ratio of 1%–6% is required. The results show that the temperature gradients and thermal stresses of stainless steel are significantly higher than those of aluminium and copper. From the standpoint of thermal stress, copper is recommended as the tube receiver material. Using Al2O3 in water as an HTF increases the average output temperature by 2%, 6%, and 10% under volume concentrations of 0%, 2%, and 6% respectively. The study concluded that the thermal efficiency increases from 3% to 14% for nanoparticle volume fractions ranging from 2% to 6%.